Cell-Based Therapies for Heart Failure - Campos de Carvalho, Antonio Carlos; Kasai-Brunswick, Tais H.; Bastos Carvalho, Adriana (Frontiers in Pharmacology, 2021)
Heart failure has reached epidemic proportions with the advances in cardiovascular therapies for ischemic heart diseases and the progressive aging of the world population. Efficient pharmacologic therapies are available for treating heart failure, but unfortunately even with optimized therapy prognosis is often poor. Their last therapeutic option is, therefore, heart transplantation with limited organ supply and complications related to immunosuppression. In this setting, cell therapies have emerged as an alternative therapy. Many clinical trials have now been performed using different cell types and injection routes. In this perspective, we will analyze the results of such trials and discuss future perspectives for cell therapies as an efficacious treatment of heart failure.